2004
DOI: 10.1002/jbm.b.30010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat pressing on the mechanical properties of a mica‐based glass‐ceramic

Abstract: Previous work has shown that heat pressing of mica-based glass-ceramics can lead to crystal alignment along the direction of pressing. The purpose of this study was to evaluate the effect of heat pressing on the fracture toughness of mica-based glass-ceramics. Glass rods (12 x 60 mm) were prepared by melting the glass composition at 1400 degrees C for 2 h. Ingots (12 x 12 mm; n = 5) and discs (12 x 1.5 mm; n = 10) were cut from the rods. The discs were heat treated to simulate heat pressing and served as contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Uno et al and Qin et al substituted K + or Na + with Ba 2+ or Ca 2+ as the interlayer ions of mica crystals, which resulted in the formation of high‐strength mica glass‐ceramics . Oriented mica glass‐ceramics fabricated by hot‐pressing or extrusion processes had higher strength and toughness than the conventional castable mica glass‐ceramics that contained randomly oriented mica crystals with a house‐of‐cards structure . In addition, these materials could be reinforced with ZrO 2 crystallized from the bulk glass .…”
Section: Restorative Dental Glass‐ceramics (Rdgcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Uno et al and Qin et al substituted K + or Na + with Ba 2+ or Ca 2+ as the interlayer ions of mica crystals, which resulted in the formation of high‐strength mica glass‐ceramics . Oriented mica glass‐ceramics fabricated by hot‐pressing or extrusion processes had higher strength and toughness than the conventional castable mica glass‐ceramics that contained randomly oriented mica crystals with a house‐of‐cards structure . In addition, these materials could be reinforced with ZrO 2 crystallized from the bulk glass .…”
Section: Restorative Dental Glass‐ceramics (Rdgcs)mentioning
confidence: 99%
“…55,56 Oriented mica glassceramics fabricated by hot-pressing or extrusion processes had higher strength and toughness than the conventional castable mica glass-ceramics that contained randomly oriented mica crystals with a house-of-cards structure. [57][58][59][60][61] In addition, these materials could be reinforced with ZrO 2 crystallized from the bulk glass. [62][63][64][65][66] It has been reported that a calcium mica-based nanocomposite containing nano-size (20-50 nm) tetragonal-ZrO 2 particles exhibits notably a high flexural strength (500 MPa) and fracture toughness ).…”
Section: Mica-based Glass-ceramicsmentioning
confidence: 99%
“…Sintering may result in the introduction of thermally induced residual stresses [22] which can result in the deformation of the ceramic body [24] and a modification of the measured BFS [24,26]. It has been suggested that heat-pressing fabrication routes for glass-ceramic materials are advantageous by reducing the likelihood of the formation of large flaws [27,28] and minimising thermally induced residual stresses [22]. A further important clinical influence on restoration fracture resistance is the impact of cementation protocols which may modify surface defect distributions [29][30][31] Therefore, the aim of the current study was to investigate the effect of heat-pressing and subsequent pre-cementation (acid-etching) and resin-cementation operative M a n u s c r i p t 3 techniques on the development and magnitude of the transient and residual stresses in different clinically relevant thicknesses of a lithium disilicate glass-ceramic characterised using a profilometric technique [23][24][25].…”
Section: *Manuscript Without Author Detailsmentioning
confidence: 99%
“…Sintering may result in the introduction of thermally induced residual stresses 22 which can result in the deformation of the ceramic body 24 and a modification of the measured BFS. 24,26 It has been suggested that heat-pressing fabrication routes for glassceramic materials are advantageous by reducing the likelihood of the formation of large flaws 27,28 and minimising thermally induced residual stresses. 22 A further important clinical influence on restoration fracture resistance is the impact of cementation protocols which may modify surface defect distributions [29][30][31] and transient and residual stress states.…”
Section: Introductionmentioning
confidence: 99%